Assessment of periodontitis vaccine using three different bacterial outer membrane vesicles in canine model - Ryoma Nakao; Takehiro Yamaguchi; Haruka Shibasaki; Jun Saeki; Aoi Takahashi; Ryunosuke Tominaga; Kimihiro Abe; Yukihiro Akeda; Tomoyo Nakagawa-Nakamura; Tomohiko Nishino; Kazuyuki Ishihara; Atsushi Jinno-Oue; et al. (mSphere)
ABSTRACT Canines frequently develop periodontitis, which is similar and relevant to immunopathology and microbiology of human periodontitis. The aim of this study was to investigate whether bacterial outer membrane vesicle (OMV)-based periodontal vaccines induced humoral immune response in canines from a human vaccine development perspective. Porphyromonas gingivalis (Pg) and Treponema denticola (Td), two major periodontal pathobionts, were chosen as vaccine targets. Intranasal (IN) immunization with Pg OMVs and Td OMVs strongly elicited humoral immune responses against the two respective species in preparative mouse experiments, particularly when adjuvanted with a probiotic Escherichia coli derivative (EcNΔflhD)-derived OMVs. However, in beagles, intranasal immunization with the same Pg/Td/EcNΔflhD OMV vaccine insufficiently elicits humoral immune responses. Nevertheless, the subcutaneous booster with the same OMVs dramatically improved antibody responses in both systemic blood circulation and mucosal sites such as eyes, oral cavity, and upper and lower respiratory tracts. Metagenomic analysis of salivary microbiota revealed that the OMV vaccine might change the microbial composition, while not reducing the number of any periodontal pathobionts at least during the timeframe of the present beagle study. In in vitro Pg growth inhibition assay, serum samples from OMV-immunized beagles significantly inhibited growth of the gingipain-deficient strain but not the gingipain-expressing wild-type strain. Taken together, our data offer the trivalent OMV vaccine strategy by IN-prime/SC-boost regimen, which could elicit robust mucosal immune responses, while suggesting the requirement of revised periodontal vaccine regimen toward achievement of sterilizing immunity in the oral cavity.IMPORTANCEBacterial outer-membrane vesicles (OMVs) are attractive for use as novel nanoparticle adjuvants, as well as delivery platforms. Periodontal diseases are the most prevalent oral diseases in humans and have serious health and economic burdens, greatly reducing quality of life. The aim of this study is to investigate the humoral immune responses to an OMV-based periodontal disease vaccine in beagles. The vaccine elicited strong mucosal immune responses when administered to beagles by a four-dose heterologous immunization (IN-IN-IN prime and subcutaneous [SC] boost). The OMV vaccine significantly altered the composition of the microbial community in the oral cavity. These findings suggest the utility of the intranasal (IN) prime followed by the SC boost regimen as a rational option to elicit robust humoral immune responses in canines, and most probably in humans as well. We here discuss the outcomes of beagle experiments, the mechanism behind immunological escape of Pg from host immunity, and a rational perspective toward sterilizing immunity in the oral cavity.